Spectrum wars : the policy and technology debate - Manner, Jennifer A. (Artech House telecommunications library., 2003)
Staking a claim in the radiocommunications spectrum is of critical importance as more and more telecommunications companies turn to wireless services to sustain profitability, and in some cases even maintain viability. To ensure your company wins the battle for this limited resource, this unique new book helps you ... Thoroughly understand the radiocommunications spectrum resource, how it is allocated, and the regulatory regime governing it. Formulate efficient, cost-effective plans for obtaining access and approval to operate in frequency. Master the lobbying, technical, regulatory, legal, and political skills needed for success. Comprehend the growing variety of difficult policy challenges in the spectrum arena, including the use of secondary spectrum markets. Gain valuable insight into how telecom's financial meltdown is impacting the battle for spectrum. Radiocommunications spectrum is a limited resource and there will always be a struggle over how it is allocated and utilized. Spectrum Wars: The Policy and Technology Debate is insurance, helping you and your company succeed in this struggle.